REPRESENTASI MAKNA BHINEKA TUNGGAL IKA DALAM LIRIK IKLAN INDOMIE EDISI SATU SELERA - Yanti, Fitri; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In a work of song there are elements that are important in addition to musical arrangements. One of the most important things in a music is the existence of the lyrics of the song even just short song. Trough song lyrics written by listeners songwriters are invited to interpret through the brain that stores experience and knowledge an process it as a basic foundation in disgeting beauty of the song lyrics. This study aims to express the meaning of denotation, connotation, an the myth of Bhineka Tunggal Ika messages contained in the lyrics of Indomie advertisement edition one taste.Research metodh used is semiotic analysis of Roland Barthes, research uses a qualitative, the subject of this reseach the lyrics of Indomie advertisement edition one taste. The object of the research is the meaning of denotation, connotation,and myth in the lyrics of Indomie advertisement edition one taste. In data collecting researcher using documentation technique an literature study.The result of research, in denotation : that we are all unique and though different Indonesian nation like Indomie. Connotation : humans are multicultural beings but here it is said that Indomie remains a common choice, and myth :god created none of the same humans beings so nation and uphold the attitude of tolerance and mutual respect, also the people of Indonesia had previously the same taste of Indomie wich is a populer since long.Keyword : Bhineka tunggal Ika, lyrics Indomie, representation